2011
DOI: 10.1093/ecam/nep147
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activity of 2‐methoxy‐1,4‐naphthoquinone and Stigmasta‐7,22‐diene‐3β‐ol from Impatiens balsamina L. against Multiple Antibiotic‐Resistant Helicobacter pylori

Abstract: Infection with Helicobacter pylori is strongly associated with gastric cancer and gastric adenocarcinoma. WHO classified H. pylori as a group 1 carcinogen in 1994. Impatiens balsamina L. has been used as indigenous medicine in Asia for the treatment of rheumatism, fractures and fingernail inflammation. In this study, we isolated anti-H. pylori compounds from this plant and investigated their anti- and bactericidal activity. Compounds of 2-methoxy-1,4-naphthoquinone (MeONQ) and stigmasta-7,22-diene-3β-ol (spina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 38 publications
1
16
0
3
Order By: Relevance
“…This result is in agreement with a previous study by Yang and others (2001) who reported that 2‐methoxy‐1,4‐naphthoquinone and a crude I. balsamina extract possessed significant antimicrobial activity against 12 bacterial strains and 8 fungal strains. Our results about the antimicrobial activity of I. balsamina are similar to other reports about this plant (Thevissen and others 2005; Lim and others 2007; Ding and others 2008; Sengottuvel and others 2010; Mori and others 2011; Wang and others 2011). In addition, Sakunphueak has compared the antimicrobial activities of three naphthoquinones in the leaves of I. balsamina and reported that these naphthoquinones might be the main active compounds which respond to the antimicrobial potentials (Sakunphueak and Panichayupakaranant 2010; Sakunphueak and Panichayupakaranant 2011).…”
Section: Resultssupporting
confidence: 92%
“…This result is in agreement with a previous study by Yang and others (2001) who reported that 2‐methoxy‐1,4‐naphthoquinone and a crude I. balsamina extract possessed significant antimicrobial activity against 12 bacterial strains and 8 fungal strains. Our results about the antimicrobial activity of I. balsamina are similar to other reports about this plant (Thevissen and others 2005; Lim and others 2007; Ding and others 2008; Sengottuvel and others 2010; Mori and others 2011; Wang and others 2011). In addition, Sakunphueak has compared the antimicrobial activities of three naphthoquinones in the leaves of I. balsamina and reported that these naphthoquinones might be the main active compounds which respond to the antimicrobial potentials (Sakunphueak and Panichayupakaranant 2010; Sakunphueak and Panichayupakaranant 2011).…”
Section: Resultssupporting
confidence: 92%
“…Salah satu tanaman yang saat ini dapat dimanfaatkan sebagai antibakteri yaitu tanaman pacar air (Impatiens balsamina L.). Penelitian yang telah dilakukan menunjukkan bahwa ekstrak pacar air memberikan efek antibakteri terhadap Propionibacterium acnes, di mana senyawa yang berperan dalam aktivitas antibakteri adalah flavonoid dan naftokuinon (11). Aktivitas antibakteri yang baik dari tanaman pacar air menunjukkan potensinya untuk digunakan sebagai antijerawat.…”
Section: Pendahuluanunclassified
“…Two new fl avone glycosides isolated from the seeds were determined as quercetin- (Lei et al 2010 ). 2-Methoxy-1,4-naphthoquinone (MeONQ) abounds in the I. balsamina pod at the level of 4.39 % (w/w db) (Wang et al 2011 ). Eight major baccharane glycosides, namely, hosenkosides A, B, C, F, G, K, L and M, were isolated from the seeds .…”
Section: Fruit/seed Phytochemicalsmentioning
confidence: 99%
“…This activity exceeded that of metronidazole and approximated to that of amoxicillin. 2-Methoxy-1,4-naphthoquinone (MeONQ) and stigmasta-7,22-diene-3β-ol (spinasterol) isolated from the pods and roots/stems/leaves of I. balsamina , respectively, exhibited anti-H. pylori (Wang et al 2011 ). The minimum inhibitory concentrations (MICs) and minimum bactericidal concentrations (MBCs) for MeONQ were in the ranges of 0.156-0.625 and 0.313-0.625 μg/ml, respectively, and in the ranges of 20-80 μg/m both of MICs and MBCs for spinasterol against antibiotic (clarithromycin, metronidazole and levofl oxacin)-resistant Helico bacter pylori .…”
Section: Antimicrobial Activitymentioning
confidence: 99%